Nanoparticles Applications in Time-Temperature Indicators (TTIs) for cold chain validation of fruits in Cundinamarca region (2023)
New functional Time-Temperature Indicators (TTIs) utilizing silver and gold nanoparticles (AgNPs and AuNPs) have been fabricated to validate the cold chain compliance of fruits (with temperature requirements ranging between 0°C and 4°C) in the Cundinamarca Region. The working principle of these indicators is built around plasmonic nanoparticles (NPs) and relies on their Localized Surface Plasmon Resonances (LSPRs). The plasmonic sensing approach is based on a spectral shift of the plasmon resonance of NPs that are suspended within a medium (nanodispersion), which responds to temperature variations. The temperature alters the initial configuration of the NPs as time progresses, leading to variations in their LSPRs. This phenomenon becomes evident at a larger scale as an optical response, characterized by a colorimetric change in the nanodispersion. In this study, we identify three mechanisms of physical activation responsible for inducing a colorimetric change response in the nanodispersions at temperatures relevant to fruits’ cold chain monitoring. Furthermore, we explore their potential application in fabricating functional Time-Temperature Indicators (TTIs), which are defined in this thesis as indicators composed of a nanodispersion (active material) and a container. The characterization was conducted at three levels: nanodispersions, containers, and TTIs. This work investigated the correlation between the temperature response and parameters such as type of NPs, size, NPs’ synthesis route, and concentration in the performance of TTIs based on nanodispersions. The nanodispersions of AgNPs and AuNPs were synthesized using chemical and physical methods. Specifically, AgNPs were chemically synthesized using two distinct approaches: the in-situ reduction method and the seed-based thermal synthetic method (the nanoparticles synthesized by the latter method were labeled as AgTNPs); while AuNPs were synthesized through the Pulsed Laser Ablation in Liquid Technique. The quantification of the optical response of the nanodispersions was obtained at temperatures of 4°C and 22°C for 5 hours to simulate a break in the fruits’ cold chain conditions. At 4°C, both AgNPs and AgTNPs exhibited color constancy, but at 22°C, they displayed significant variations in colorimetric responses, reaching up to 252 %. On the other hand, AuNPs showed colorimetric responses at low temperatures (4°C), with colorimetric variations of up to 27 %. Characterization techniques such as UV-visible Spectroscopy (UV-Vis), Scanning Electron Microscopy (SEM), Energy Dispersive X-ray Spectrometry (EDS), Dynamic Light Scattering (DLS), and Nanoparticle Tracking Analysis (NTA) were used to determine the mechanisms by which the nanodispersions change their optical response upon exposure to the temperatures under study. The research revealed that for AgNPs, the mechanism is based on an increase in the concentration of NPs in the nanodispersion, from 6.82·108 to 9.90·109 NPs/mL. This mechanism is based on how the synthesis method (chemical reduction) depends on temperature. The process converts metallic ions into nanoparticles by reducing chemical precursors. As the temperature increases, the reduction reaction rate also increases due to higher kinetic energy of the molecules involved. For AgTNPs, the operational mechanism presented is rooted in the variation of the geometry of a certain percentage of NPs, leading to heterogeneity in NPs LSPR. For these AgTNPs, AgNPs seeds were utilized, acting as nuclei onto which additional Ag is deposited, enabling controlled growth and formation of new nanoparticles with shapes strongly influenced by exposure time and temperature. In the case of AuNPs, the colorimetric change mechanism was found to be related to agglomeration processes. At low temperatures, the average interparticle distances between nanoparticles decrease, and the electrostatic interactions among the NPs intensify, leading to the agglomeration of nanoparticles. Consequently, a plasmonic coupling effect occurs, resulting in a collective colorimetric response. Regarding the container, 3D-printed containers using Plant-based Resin, suitable for incorporating the nanodispersions, were also fabricated. These containers demonstrated appropriate transparency in the visible range, thermal conductivity, and impermeability for TTI manufacturing. Among the different TTIs, those based on AgTNPs showed the most distinguishable colorimetric changes at 22°C, with a total color difference of 39.9. Finally, through a comparison of the activation energies required for fruit degradation and the activation energy for the colorimetric change of the TTIs, it was possible to project that the manufactured TTIs could be suitable for monitoring various fruits, including strawberries, apples, blackberries, pears, passionfruits, bananas, peaches, and cape gooseberries. This research highlights the significant potential of nanotechnology in enhancing cold chain monitoring by offering easily interpretable colorimetric indicators.